O-085 School-Age Outcomes Among IVF-Conceived Children: A Causal Inference Analysis Using Linked Population-Wide Data. (30th June 2022) - Kennedy, A; Vollenhoven, B; Hiscock, R; Stern, C; Walker, S; Cheong, J; Quach, J; Hastie, R; Wilkinson, D; McBain, J; Gurrin, L; Tong, S; et al.
Abstract: Study question: To determine the causal effect of in-vitro fertilisation (IVF) on primary school-age childhood developmental and educational outcomes, compared with outcomes following spontaneous conception. Summary answer: The school-age developmental and educational outcomes for children conceived by IVF are equivalent to those of spontaneously conceived peers. What is known already: More than 8 million children have been conceived globally with the assistance of in-vitro fertilization (IVF). Large cohort studies have suggested an increase in the frequency of congenital abnormalities, autism spectrum disorder, developmental-delay and intellectual disability in children conceived via IVF. Educational and cognitive outcomes following IVF conception have not yet been adequately established. Two large Scandinavian studies (Norrman et al 2018 and Wienecke et al 2020) found poorer educational outcomes in children born after IVF-conception. Study design, size, duration: Causal inference methods (based on the potential outcomes approach) were used to analyse observation data in a way that emulates the results of a target randomised clinical trial. The study cohort comprised state-wide linked maternal and childhood administrative data from Victoria, Australia. Participants/materials, setting, methods: The study included singleton infants conceived spontaneously or via IVF and born between 2005-2014. The exposure of interest was conception via IVF, with those born after spontaneous conception as the control group. Two separate measures of childhood outcome were examined: The Australian Early Developmental Consensus (AEDC), (age 4-6); and the National Assessment Program – Literacy and Numeracy (NAPLAN) at age 7-9. We combined inverse probability weighting with regression adjustment to estimate population average causal effects. Main results and the role of chance: The final cohort included 412, 713 children across the two outcome cohorts. Linked records were available for 4, 697 IVF-conceived cases and 168, 503 controls for AEDC outcome data, and 8, 976 cases and 333, 335 controls for NAPLAN data. The mothers of IVF-conceived children were older, more highly educated mothers, who lived in more socio-economic advantaged areas and were less likely to be from non-English speaking backgrounds. There was no causal effect of IVF-conception on the on the risk of developmental vulnerability at school-entry compared to spontaneously conceived children, as defined by AEDC metrics; with an adjusted risk difference of -0.3% (95% CI -3.7% to 3.1%) and an adjusted risk ratio of 0.97 (95% CI 0.77 to 1.25). At age 7-9 years, there was no causal effect of IVF-conception on the NAPLAN overall z-score, adjusted mean difference of 0.030 (95% CI -0.018 to 0.077) between IVF-conceived and spontaneously conceived children. Given the use of observational data, there were missing data and inherent differences in the covariate profile of the exposure cohorts. Multiple imputation and doubly robust inverse probability weighting regression adjustment modelling was utilised to allow a causal interpretation of results. Limitations, reasons for caution: Children who did not attend school due to severe disability were not included, possibly leading to selection bias. It is possible that unmeasured common cause confounders could have led to bias in estimating the average treatment effects. Wider implications of the findings: This study, in contrast to previous evidence, suggests that conception via IVF does not affect early childhood developmental and educational outcomes. These findings provide important reassurance for current and prospective parents, and clinicians alike. Trial registration number: Not applicable